Aplikasi Peta Kendali p sebagai Pengendalian Kualitas Karet di PTPN IX Batujamus/Kerjoarum - Isti Khomah; Endang Siti Rahayu (Universitas Muhammadiyah Yogyakarta, 2015)
The increasing of global rubber consumption is an opportunity as well as a challenge for Indonesian rubber produsers to increase the quantity and the quality of production. Faced the competition between countries, the quality of rubber products should be enhanced adapted to consumer demand. This study aims to determine whether the quality of the rubber produced in PTPN IX (Persero) Garden Batujamus/Kerjoarum still within the control or not. This study uses time series data, in the form of rubber production data during March 2012 - February 201, that were analyzed descriptively using Control p Chart Analysis. Control p Chart describe the proportion of production damage that can be tolerated as a tool for statistical Control p Chart Application as Quality Control Tools for Rubber Production in PTPN IX Batujamus/Kerjoarum process control. This study shows that the quality of the rubber produced by PTPN IX (Persero) Garden Batujamus/ Kerjoarum is out of the control. The Control p Chart proves that there are still many points that are outside the production control line. The production domination of the third RSS type (RSS 3) cause this problem, so that the profit and the efficiency of the company can be increased if the RSS 3 product can be controlled and be changed with the production of RSS 1.